The Effect of the GASING Method Supported by Siri Local Media on Elementary School Students’ Mathematics Learning Motivation - Wisye Souhoka; Wigati Yektiningtyas; Ronaldo Kho; Okky Riswandha Imawan (The Future of Education Journal, 2026)
Mathematics learning in elementary schools continues to face challenges, particularly regarding students' low learning motivation, which often affects their participation and academic achievement. This study aimed to analyze the effect of the GASING (Easy, Fun, and Enjoyable) method assisted by Siri local media on the mathematics learning motivation of fourth-grade students at SD YPK Alfa Omega Waisai, Raja Ampat. The study employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The participants consisted of 60 fourth-grade students divided into an experimental group (30 students) and a control group (30 students). Data were collected through a mathematics learning motivation questionnaire and analyzed using descriptive statistics, normality and homogeneity tests, and an Independent Sample t-Test. The findings revealed that the experimental group experienced a substantial increase in learning motivation, with the mean score rising from 67.13 to 82.47, while the control group increased from 66.87 to 71.23. The results of the hypothesis test showed a t-value of 4.872 and a significance value of 0.000 (p < 0.05), indicating a statistically significant difference between the two groups. These findings demonstrate that the implementation of the GASING method supported by Siri local media effectively enhances students’ mathematics learning motivation. The integration of an interactive learning approach with culturally relevant local media creates a more engaging, contextual, and meaningful learning experience for elementary school students. Therefore, the GASING method assisted by Siri local media can be considered an effective alternative for improving mathematics learning motivation in elementary education.